Carbon Credit Mechanisms: A Market Based Approach to Climate Mitigation - V. Nandhini; R. Venkataraman (Archives of Current Research International, 2025)
Introduction: Climate change is mainly caused by human activities, and it results in the release of harmful greenhouse gases like carbon dioxide, methane, and nitrous oxide into the atmosphere. Among the various sources of ‘C’ emission, electricity and heat generation is the major activity both in the World (32.25 percent) as well as in India (35.86 per cent) where Agriculture acts as the fourth major player of CO2 emission in the World (11.60 per cent) and in India, it has a dominant role which stand in second position with 21.92 per cent share. Rising GHG emissions, especially from electricity and agriculture, pose a major climate challenge in India. Though carbon markets offer a tool for mitigation, awareness and participation remain limited. Understanding carbon trading mechanisms is essential to enhance their role in reducing emissions. Objectives: To know the different carbon trading mechanism to mitigate carbon emission. Carbon Market: In simple terms, the carbon market is buying and selling carbon credits; each credit indicates one ton of carbon dioxide (or similar gases) that’s been removed from the atmosphere or prevented from being released. These credits can be traded at both national and international carbon markets. There are two main types of carbon markets: compliance markets and voluntary markets. Major Findings: Compliance Market: The compliance market is run under the certain rules and regulations, which is given by the United Nations Framework Convention on Climate Change (UNFCCC). It’s backed by regulations and helps monitor emissions across countries and industries. India issued approximately 106 million tons (MT) of CO₂ emissions upto mid-2024. Voluntary Market: The voluntary carbon market is designed for those who choose to act on climate change, even when they’re not legally required to. Whether it’s businesses, organizations, or individuals, they can purchase carbon credits to support initiatives such as reforestation or clean energy projects. India issued approximately 43.4 MT carbon credits in 2024, making it the second-largest issuer globally after the United States. Conclusion: This dual engagement reflects not only India’s dedication to reducing emissions but also its strategic approach to integrating economic incentives with environmental responsibility, thereby supporting its broader goals for sustainable development and a low-carbon future.